2021
DOI: 10.1038/s41385-021-00423-5
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of the IL2RA locus causes excessive IL-2 signaling and may predispose to very early onset colitis

Abstract: Single genetic mutations predispose to very early onset inflammatory bowel disease (VEO-IBD). Here, we identify a de novo duplication of the 10p15.1 chromosomal region, including the IL2RA locus, in a 2-year-old girl with treatment-resistant pancolitis that was brought into remission by colectomy. Strikingly, after colectomy while the patient was in clinical remission and without medication, the peripheral blood CD4:CD8 ratio was constitutively high and CD25 expression was increased on circulating effector mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 43 publications
(55 reference statements)
1
17
0
Order By: Relevance
“…These mutations may have differential effects on Treg cells versus effector T cells as CD25 deficiency results in defective IL-10 expression in CD4 + T cells (267) and lack of IL-10 expression by Treg cells in mice contributes to intestinal inflammation (46). Recently, a microduplication of the IL2RA locus associated with very-early-onset IBD which is attributed to increased IL-2 signaling (270). This increased IL-2 signaling potentiates the IFNg response after TCR activation (270,271).…”
Section: Monogenic Disorders Driven By Treg Cell Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…These mutations may have differential effects on Treg cells versus effector T cells as CD25 deficiency results in defective IL-10 expression in CD4 + T cells (267) and lack of IL-10 expression by Treg cells in mice contributes to intestinal inflammation (46). Recently, a microduplication of the IL2RA locus associated with very-early-onset IBD which is attributed to increased IL-2 signaling (270). This increased IL-2 signaling potentiates the IFNg response after TCR activation (270,271).…”
Section: Monogenic Disorders Driven By Treg Cell Dysfunctionmentioning
confidence: 99%
“…Recently, a microduplication of the IL2RA locus associated with very-early-onset IBD which is attributed to increased IL-2 signaling (270). This increased IL-2 signaling potentiates the IFNg response after TCR activation (270,271).…”
Section: Monogenic Disorders Driven By Treg Cell Dysfunctionmentioning
confidence: 99%
“…IL-2, as a Th1-type cytokine, is critical for maintaining intestinal homeostasis. However, high expression of the IL-2 signaling pathway could predispose to colonic intestinal inflammation [ 46 ]. Our current results indicated that r Cs CP or Cs CA might down-regulate the inflammatory responses of colitis mice via elevating Treg cells in both the spleens and MLNs, inducing the release of Th2 cytokines (IL-10, IL-4 and IL-13), and restraining the production of IL-1β and IL-2 cytokines in serum.…”
Section: Discussionmentioning
confidence: 99%
“…This is the case in human patients as well as in mouse models of SLE [ 39 , 74 ]. However, with regard to IBD, enhanced IL-2 signaling may predispose to disease manifestation as shown by a very early onset refractory colitis, in which a duplication of CD25 was found, which causes excessive STAT5 signaling [ 75 ]. Thus, IL-2 might be a double edged sword in the context of inflammation since it also boosts effector T cell proliferation.…”
Section: Therapies Affecting Tregs In Autoimmune Diseasesmentioning
confidence: 99%